Acidification of mixtures of granite powder and compost for reuse in plant production. Issue 1 (2nd January 2016) - Paradelo, Remigio; Vázquez-Nion, Daniel; Silva, Benita; González, Ángela; Barral, María Teresa
ABSTRACT: We evaluated the utilization of granite powder—a residue of stone cutting and polishing resulting from its preparation for construction and ornamental use—in the preparation of nursery potting mixtures, within a general objective of waste recycling and reuse. Granite powder was blended with two composts of different origins and properties: one elaborated from the organic fraction of municipal solid waste (MSW), and another from pine bark. Since all materials presented pH values over 8, which are excessive for growing most vegetal species, the use of iron sulphate to acidify them has been assessed. Three doses of iron sulphate (14, 69, and 97 g kg −1, equivalent to 0.1, 0.5, and 0.7 meq H + g −1 ) were added to the granitic powder and mixtures with 25 or 75% (v/v) of each compost, which were incubated in the laboratory during 30 days. Doses of iron sulphate above 0.1 meq H + g −1 resulted in excessive electrical conductivity (>2 dS m −1 ) in all the samples, and too low pH values (<5) in most of them. The productivity of granite powder/compost mixtures acidified with 0.1 meq H + g −1 was tested in a greenhouse experiment with ryegrass, where it was observed that plant productivity increased with respect to a control commercial substrate based on peat, in particular when the MSW compost was employed. On the basis of the physicochemical properties of the mixtures and the results of the greenhouse experiment, the use of granite powder mixed with 75% of MSW compost (v/v), acidified with 14 g kg −1 of iron sulphate (0.1 meq H + g −1 ) is recommended.